Nano-black phosphorus for combined cancer phototherapy: recent advances and prospects. (29th March 2018) - Yang, Xiaoyan; Liu, Gongyuan; Shi, Yunhao; Huang, Wei; Shao, Jinjun; Dong, Xiaochen
Abstract: Black phosphorus (BP), emerging as a new member of two-dimensional nanomaterials, has attracted growing research interests for its amazing photoelectric properties and promising application in electronic devices. Recently, BP has been confirmed to be a desirable candidate for phototherapy against cancer, including photothermal therapy and photodynamic therapy. By regulating the number of layers, the bandgap of BP nanosheets (NSs) can be finely tuned to present near infrared light triggered phototherapeutic behaviors. Furthermore, the exfoliated nano-sized BP also exhibits excellent tumor-targeting property as a nanomedicine via the enhanced permeability and retention effect. With biodegradable nature and outstanding therapeutic performance, BP is highly expected to be developed as novel anti-cancer agents as well as a potential carrier for advanced cancer theranostics. In this review, on the basis of summarizing the recent advances of BP in biomedical applications, the size and layer effects of BP on its targeting effect and phototherapeutic performance are discussed. Then, the rationally designed multifunctional nanoplatforms based on BP are introduced. And, the remaining challenges and prospects of nano-BP for clinic applications against cancer are discussed and outlooked.